The affective atmosphere of rural life and digital healthcare: Understanding older persons’ engagement in eHealth services - Lindberg, Jens; Lundgren, Anna Sofia (Journal of rural studies, 2022)
The implementation of digital healthcare technologies—eHealth—is presented as a solution to increasing costs, demographic changes, and quality issues in rural healthcare. Employing the concept of affective atmospheres, this article uses interviews to explore the emotional aspects of digital healthcare among rural persons of advanced age. Our results suggest that participants were clearly influenced by an affective atmosphere that was deeply embedded in spatial imageries as well as in notions of old age. Strong feelings of resignation, necessity, low entitlement, and defiance tended to encourage participants’ wishes for local face-to-face healthcare to translate into viewing eHealth solutions as positive. This also meant that participants came to enact neoliberal identities of “active ageing”. In conclusion, the concept of affective atmospheres highlights how human subjects and digital materialities interact in the production of human emotional responses to digital healthcare technologies, and emphasises how the conditions and shared imageries of geographic space and age are active components in that process. •Responses to rural eHealth are influenced by spatially embedded affective atmosphere.•Responses to rural eHealth are influenced by age-sensitive cultural imageries.•Rural affective atmosphere encouraged seeing eHealth solutions as positive.•Rural affective atmosphere made territorial inequalities seem sensible.•Rural affective atmosphere reproduced neoliberal subjectivities of active ageing.